A Rare Case of Primary Renal Lymphoma: Case report - Mahat, Smritee; Manandhar, Usha; Bhatta, Maya; Shrestha, Sonafi; Sharma, Amit; Gaire, Prabin; Sayami, Gita; Sharma, Amit (Journal of Karnali Academy of Health Sciences, 2019)
The kidney is one of the most common sites for extranodal lymphoma. Most often renal lymphoma is seen as a part of the disseminated lymphomatous disease. Primary renal lymphoma is a rare entity. Usually, patients are asymptomatic and are identified incidentally. This leads to the late presentation of the case. We present a case of 55 years male, who was evaluated for right upper quadrant pain. Radiologically, the case was diagnosed as renal cell carcinoma with hepatic metastases. Subsequent tests and biopsy were performed. Histopathology and immunohistochemistry revealed diffuse large B cell lymphoma with positivity for CD20, CD45, PAX5 and Bcl2 and negativity for CD3, CD5, CD10, CD23, CD30, Bcl6, CyclD1, and MUM1. The patient could be treated with chemotherapy but we lost to follow up.